Effect of Ultrasonic Penetration with Volatile Oil of Olibanum and Chuanxiong Rhizoma on Acute Knee Synovitis Induced by Sports Training: An Open-Label Randomized Controlled Study - Qiwen Xuan; Yi Ruan; Chengbing Cao; Zifei Yin; Juan Du; Can Lv; Fanfu Fang; Wei Gu (Pain Research and Management)
Background. Knee synovitis is a common sports injury. We proposed the use of UTVOR, which is a combination of the use of volatile oil of Olibanum (VOO) and volatile oil of Chuanxiong Rhizoma (VOCR) and conventional ultrasound (US) therapy, to treat knee synovitis. Design, Setting, Participants, and Interventions. Participants were randomly assigned into a control group (conventional US therapy group) and a test group (UTVOR group). The control group received conventional US therapy with a coupling agent as the medium. The test group received a revised US therapy with VOO and VOCR as media. Both groups were treated once per day for three consecutive days. Main Outcome Measures. The subjects’ Visual Analogue Scale (VAS) pain score, Lysholm knee score, knee swelling degree, circumference, and range of motion of the knee joint were evaluated before the first treatment and 24 h after the third treatment. The VAS pain score was considered the primary outcome, while the three other measurements were regarded as the secondary outcomes. An adverse event was reported subjectively and recorded. Results. A total of 116 participants were included in the analysis (test group: n = 64; control group: n = 52). The evaluation results showed that the VAS pain scores of the male and female participants in both groups decreased after treatment (P<0.001), but only the difference among the male sub-group had significant between-group difference (P<0.001). After treatment, the Lysholm scores in both groups increased significantly (all P<0.001), the range of motion and the circumference of the injured knee decreased significantly (P<0.001), while no between-group difference was observed in general or in the gender sub-groups (all P>0.025). No side effect or complication was reported during the treatment. Conclusion. UTVOR had a superior analgesic effect to conventional US therapy in the male population, but its effects on alleviating joint function, swelling, and range of motion were comparable to that of conventional US therapy. Our study found that UTVOR can be an effective method to reduce pain and treat knee synovitis, and it is subjectively safe. Trial registration. This study was registered under the Chinese Clinical Trial Registry (Trial Registration Number: ChiCTR2000035671).